Design Of a Website-Based Information System for Optimizing UMKM Product Marketing Using the Waterfall Method - Heni Wulandari; Suherman Suherman (Sean Institute, 2026)
This study addresses the marketing challenges faced by “Risol Jiya,” a micro, small, and medium enterprise (UMKM) in Langkat Regency, which has not yet optimized a website as its primary marketing channel, resulting in limited market reach and low brand recognition. To address this problem, this study designs a website-based information system for optimizing UMKM product marketing using the Waterfall development method, covering requirements analysis, system design (use case, activity, and sequence diagrams), implementation using PHP and a MySQL database, black-box testing, and system maintenance. Testing success is measured using a validated test-case percentage formula, while marketing effectiveness is evaluated using a before-after growth percentage formula adapted from prior digital marketing studies. The resulting system provides a home page that functions as a digital storefront, a testimonial dashboard, contact and address information, and a product ordering page that operates according to the intended requirements. The findings show that the system successfully supports the marketing process and can help the UMKM increase market reach, product visibility, customer interaction, and its overall competitiveness.